An Experimental Study on Cracking Behavior of Precracked Sandstone Specimens under Seepage Pressure - Qibin Lin; Ping Cao; Hua Wang; Rihong Cao (Advances in Civil Engineering)
This paper aims to investigate the strength and failure mechanism of fractured rock under seepage pressure. For this purpose, precracked sandstone specimens were prepared with different fissure angles, and a seepage pressure loading device was created. Together with the acoustic emission (AE) system, the loading device was adopted to perform uniaxial compression tests with or without seepage pressure. The main results are as follows. Combined with axial stress-strain curves, photographic monitoring results and the output of AE counts and rock failure process can be generally divided into four stages: microcrack closure, elastic deformation, crack growth and propagation, and final failure. The seepage pressure had a significant effect on the mechanical properties of the specimens: the specimens under seepage pressure lagged far behind those without seepage pressure in peak strength but maintained a comfortable lead in peak strain. Under seepage pressure, the typical failure features of the specimens varied with the fissure angles: the specimens with small fissure angles (i.e., [0°,30°]) mainly underwent tensile failure; those with medium fissure angles (i.e., [30°,60°]) suffered from shear failure; and those with large fissure angles (i.e., [60°,75°]) were prone to tensile-shear failure.